(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
Starting from Constitutional Court Judgment No. 66/2025, which marks a halt in the Court’s evolving approach to physician-assisted dying, the contribution highlights the structural limits of a regulatory framework shaped solely through constitutional case law – an inevitably casuistic method, unable to provide the systematic coherence required by the subject. The analysis distinguishes between the value-laden definition of substantive eligibility criteria and the central role of procedural safeguards as the actual sites of protection for vulnerable individuals. In this perspective, the Canadian regulatory framework is examined critically, with particular attention to its main procedural and organisational weaknesses.